Parenting with style: Altruism and paternalism in intergenerational preference transmission - Matthias Doepke; Fabrizio Zilibotti (Institute for the Study of Labor (IZA), 2012)
We construct a theory of intergenerational preference transmission that rationalizes the choice between alternative parenting styles (related to Baumrind 1967). Parents maximize an objective function that combines Beckerian and paternalistic altruism towards children. They can affect their children's choices via two channels: either by influencing their preferences or by imposing direct restrictions on their choice sets. Different parenting styles (authoritarian, authoritative, and permissive) emerge as equilibrium outcomes, and are affected both by parental preferences and by the socioeconomic environment. We consider two applications: patience and risk aversion. We argue that parenting styles may be important for explaining why different groups or societies develop different attitudes towards human capital formation, entrepreneurship, and innovation.
Keywords: D10; J10; O10; O40; 330; intergenerational preference transmission; altruism; paternalism; entrepreneurship; innovation; Präferenztheorie; Generationenbeziehungen; Altruismus; Eltern; Pädagogik; Risikoaversion; Theorie